Tales from the dark side: A phenomenography of adult critical reflection - Stephen Brookfield (Adult Education Research Conference, 1994)
This paper attempts a phenomenography of critical reflection as it pertains to one group of adults who happen to be adult educators themselves. The adult educators whose voices are heard here were all graduates students at Teachers College, Columbia University in New York City. They are mostly female, include African Americans, Asian-Americans and Hispanic-Americans, and work in contexts as varied as the Quaker movement, the U.S. Army, IBM, psychiatric hospitals, community colleges, public schools, and universities. The sample comprises 337 educators, with 223 doctoral students majoring in adult education and 114 graduate students who have written autobiographical analyses of critical reflection episodes in seminars on critical thinking. Their stories of critical reflection are told in four ways: (1) in optional learning journals many have chosen to write during their studies, (2) in personal (office, bar, coffee shop, subway, corridor) conversations, (3) in classroom discussion during troubleshooting time explicitly allocated to making public the internal dimensions of critical reflection as a learning process, and (4) in the structured autobiographical analyses already mentioned. These stories were shared over an 11 year period, 1982-1993 and analysed qualitatively using categories of 'triggers', 'resources', 'rhythms', 'resources' and 'consequences'. As understood here, critical reflection is defined as comprising two interrelated processes: (1) learning to question, and then to replace or reframe, an assumption that is accepted by majority opinion as representing commonsense, and, (2) taking a perspective on social and political structures, or on personal and collective actions, that is strongly alternative to that held by the majority.